2014
DOI: 10.1097/mao.0000000000000616
|View full text |Cite
|
Sign up to set email alerts
|

Otologic Outcomes After Blast Injury

Abstract: Blast-related otologic injuries constitute a major source of ongoing morbidity after the Boston Marathon bombings. Continued follow-up and care of this patient population are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(42 citation statements)
references
References 28 publications
2
38
0
Order By: Relevance
“…Finally, the large pressures observed in this study suggest that hair cell loss in both the auditory (which is relatively common (45)) and vestibular systems should be expected; however, CI patients exhibiting these symptoms are seldom observed in the clinic. This disparity may result from a number of factors including: the transient nature of the pressures observed here, which are generally less damaging than an ongoing noise of comparable level; pre-existing hearing loss, which may mask new hearing loss; and the fact that vestibular injury is only seldom observed following blast exposure (46). …”
Section: Discussionmentioning
confidence: 92%
“…Finally, the large pressures observed in this study suggest that hair cell loss in both the auditory (which is relatively common (45)) and vestibular systems should be expected; however, CI patients exhibiting these symptoms are seldom observed in the clinic. This disparity may result from a number of factors including: the transient nature of the pressures observed here, which are generally less damaging than an ongoing noise of comparable level; pre-existing hearing loss, which may mask new hearing loss; and the fact that vestibular injury is only seldom observed following blast exposure (46). …”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have analyzed definitive clinical data, whereas we have examined occupational hearing conservation screening data. Military and civilian otologic and audiometric outcome data are inherently different, primarily because of the putative penultimate circumstance of the blast [26].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported minimal sensorineural hearing loss in blast-exposed individuals [5][6][7][8][9]25]; however, reversible conductive hearing losses have been more consistently identified. The greatest source of information on symptoms immediately following primary blast injury of the ear may be found in civilian literature [26]. Blast injury among civilians, however, is uncommon and generally studied as a consequence of terrorism or industrial accidents.…”
Section: Introductionmentioning
confidence: 99%
“…These patients should firstly be followed with regard to spontaneous recovery. Spontaneous closure of the perforation was found to be associated with its size, and this rate was reported to vary between 38% and 74% (7,11,12). In literature, standard tympanoplasty and, if required, tympanoossiculoplasty are the treatment methods for tympanic membrane perforations that develop after blast trauma and do not heal in the follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In literature, standard tympanoplasty and, if required, tympanoossiculoplasty are the treatment methods for tympanic membrane perforations that develop after blast trauma and do not heal in the follow-up. In patients undergoing surgery, the success rate of the graft after treatment is above 80% in many studies (7,10,11).…”
Section: Discussionmentioning
confidence: 99%